2022
DOI: 10.3389/fnut.2022.1052001
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-processed food consumption and associations with biomarkers of nutrition and inflammation in pregnancy: The Norwegian Environmental Biobank

Abstract: BackgroundA high consumption of ultra-processed foods (UPFs) is often associated with low nutritional quality, but data on associations with biomarkers are scarce. We aimed to explore associations between UPF intake, diet quality, and concentrations of biomarkers of nutrition and inflammation measured in mid-pregnancy.MethodsThis cross-sectional study included n = 2,984 pregnant women recruited during 2002–2008 in the Norwegian Mother, Father, and Child Cohort Study (MoBa). Concentrations of C-reactive protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…The current the current study also revealed notable differences in UPF consumption patterns among participants with lower family income, younger adults, overweight and people with obesity, as well as non-smokers and ex-smokers. This study aligns with previous research [41,43,44] by demonstrating that UPF consumption is inversely an inverse related to dietary quality as measured by HEI-2015, lower intake of fruits and vegetables, and positively related to total fat, cholesterol, saturated fat, and trans-fatty acid intake.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current the current study also revealed notable differences in UPF consumption patterns among participants with lower family income, younger adults, overweight and people with obesity, as well as non-smokers and ex-smokers. This study aligns with previous research [41,43,44] by demonstrating that UPF consumption is inversely an inverse related to dietary quality as measured by HEI-2015, lower intake of fruits and vegetables, and positively related to total fat, cholesterol, saturated fat, and trans-fatty acid intake.…”
Section: Discussionsupporting
confidence: 91%
“…Firstly, consumption of UPF is the predominant dietary pattern, displacing healthier foods in the American diet and globally. UPF are nutritionally inferior, poor sources of essential nutrients such as antioxidants and rich in energy, sugary drinks, saturated and hydrogenated fats [43,44]. These products all cause systemic oxidative stress and breach immunological response [50], which could be the prime mechanism for the development of many non-communicable diseases [56,57], including CRDs and cancer.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Our findings indicate that UPFs (NOVA 4) contribute 27, 29, 26.5, and 31% of total calories, total sugar, saturated fat, and sodium, respectively. Previous studies involving American, Norwegian, Brazilian, and Mexican pregnant women have estimated the proportion of UPF in total energy intake, revealing a wide range: over 50% in American women (16, 36), nearly twice the amount found in our study; 46% in Norwegian women; 27.9% in Mexican women; and 20.9% in Brazilian women (34,37,38). Furthermore, our analysis highlights the contribution of sodium, saturated fat, and sugar from UPF to the overall nutrient intake during pregnancy.…”
Section: Discussionsupporting
confidence: 50%
“…As to the E-DII score, a cross-sectional study in Brazil found a direct relationship between a higher dietary energy intake from UPF and a higher rate of dietary inflammation in pregnant women [ 58 ]. Similar findings were obtained in the Italian cohort Moli-Sani, where a higher consumption of UPF was related to a higher pro-inflammatory potential of the adults’ diet [ 59 ].…”
Section: Upf and Low-grade Inflammationmentioning
confidence: 99%